G454 The educational impact of Paediatric Palliative Simulation Study days. (7th April 2014) - Renton, K; Quinton, H; Mayer, A
Abstract : Background: The use of simulation based medical/nursing teaching is increasingly widespread. Simulation based teaching offers an immersive learning experience where professionals can practice communication and practical skills in a safe, authentic environment 1 . We designed a paediatric palliative simulation study day primarily aimed at nursing staff who manage these patients in the community/hospice. We believe this is the first of its kind in the UK. Aims: To establish whether attendance at a paediatric palliative simulation study day improved confidence and knowledge in management of common and/or difficult situations in palliative care. Method: Nurses and doctors working at local paediatric hospices or in associated specialities to palliative care were invited to attend the free one day course. Five scenarios were developed by experienced health professionals working in paediatric palliative care. On the day, participants were asked to complete a questionnaire to check basic demographic data, confidence levels, and knowledge (50 true/false questions). Following participation/observation of five scenarios they again completed the same questionnaire regarding confidence levels and knowledge. Results were analysed with Excel and XLStat using basic demographic data and Wilcoxon signed rank two-tailed test. Results: 22 nurses and three doctors have so far participated in two study days. 20/25 professionals described themselves as working primarily in palliative care. Only 8/25 had previously experienced simulation. Based on confidence questions, attendees felt more confident in managing specific end of life scenarios (p < 0.008). Based on true/false questions pre and post study day, 80% of participants improved their knowledge. The median improvement score for the cohort was 4 (p = 0.001). Conclusion: The study demonstrated a significant improvement in confidence and knowledge following the simulation course. This supports further time/financial investment in developing this type of study day. Simulation is a useful teaching adjunct in paediatric palliative care. The course also provides a valuable opportunity for professionals to network and discuss/share experiences. Reference: Cant RP, Cooper SJ. Simulation-based learning in nurse education: systematic review. J Adv Nurs 2010. 66 (1):3-15